Massive MIMO downlink based on single carrier frequency domain processing - Mokhtari, Zahra (2019)
This work was supported in part by Fundac o para a Cilncia e Tecnologia (FCT) and Instituto de Telecomunicacoes o es under the Project UID/EEA/50008/2013.